The Meena Tribe as a Subordinate Class in the Jaipur State: A Historical Study: जयपुर रियासत में उपाश्रयी वर्ग के रूप में मीणा जनजाति: एक ऐतिहासिक अध्ययन - Chamoli, Amit; Meena, Rajendra (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The present research paper, “The Meena Tribe as a Subordinate Class in the Jaipur State: A Historical Study,” aims to analyze the historical position of the Meena tribe within the social and political structure of Rajasthan. This study seeks to understand the changing historical status of the Meena community under Jaipur State. The past of the Meenas was marked with dignity, as they were not only participants in regional power but also held significant roles in local administration, land rights, and community leadership. However, with the advent of British colonial rule and policies such as the Criminal Tribes Act, along with shifts in the power structures of Jaipur State, the Meenas were classified as a “criminal tribe” and socially marginalized. This classification undermined their social prestige and severely weakened their economic and political positions. The study reveals that the institutional marginalization of the Meena tribe was the result of a deliberate and long-term strategy. Nevertheless, in the latter half of the 20th century, the community made efforts to regain its standing through education, social organizations, and political awareness. Abstract in Hindi Language: प्रस्तुत शोध पत्र “जयपुर रियासत में उपाश्रयी वर्ग के रूप में मीणा जनजाति: एक ऐतिहासिक अध्ययन” का उद्देश्य राजस्थान की ऐतिहासिक और सामाजिक संरचना के भीतर मीणा जनजाति की ऐतिहासिक स्थिति का विश्लेषण करना है। यह अध्ययन मीणा समुदाय की ऐतिहासिक स्थिति को समझने का प्रयास करता है, जो जयपुर रियासत के अंतर्गत समयानुसार बदलती रही मीणा जनजाति का अतीत गौरवशाली रहा है, जहां वे न केवल क्षेत्रीय सत्ता में भागीदार थे, बल्कि स्थानीय प्रशासन, भूमि अधिकार और सामाजिक नेतृत्व में भी उनकी महत्वपूर्ण भूमिका रही। किन्तु ब्रिटिश औपनिवेशिक शासन द्वारा अपनाई गई “क्रिमिनल ट्राइब्स एक्ट” जैसी नीतियों एवं जयपुर रियासत की सत्ता-संरचना में हो रहे बदलावों के कारण मीणाओं को ‘अपराधी जनजनजाति’ के रूप में वर्गीकृत कर, उन्हें सामाजिक रूप से बहिष्कृत किया गया। इस वर्गीकरण ने ना केवल उनकी सामाजिक प्रतिष्ठा को प्रभावित किया, बल्कि उनकी आर्थिक एवं राजनीतिक स्थितियों को भी गंभीर रूप से कमजोर कर दिया। अध्ययन से यह स्पष्ट होता है कि मीणा जनजाति को संस्थागत रूप से हाशिए पर डालने की प्रक्रिया एक सुविचारित और दीर्घकालिक रणनीति का परिणाम थी। फिर भी, 20वीं सदी के उत्तरार्ध में इस समुदाय ने शिक्षा, सामाजिक संगठनों और राजनीतिक चेतना के माध्यम से पुनः अपनी स्थिति को सुदृढ़ करने के प्रयास किए। Keywords: जयपुर रियासत, मीणा जनजाति, उपाश्रयी वर्ग, सामाजिक इतिहास, औपनिवेशिक।